Biotechnology and Bioengineering: Volume 111, Number 12, December 2014. Issue 12 (December 2014) - Unknown
<x xml:space="preserve">Abstract</x> Cover Legend Alcian blue and Sirius red stained cartilaginous pellets of human articular chondrocytes demonstrating presence of proteoglycans and collagen, respectively. See related article by Tare et al., Biotechnology and Bioengineering, Volume 111, Number 9 (September 2014), pages 1876–1885. (Image courtesy of Dr. Siwei Li and Dr. Rahul S. Tare.) <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>